Matrix metalloproteinase-9 is increased in obese subjects and decreases in response to pioglitazone - Unal, Resat; Yao-Borengasser, Aiwei; Varma, Vijayalakshmi; Rasouli, Neda; Labbate, Craig; Kern, Philip A; Ranganathan, Gouri (The journal of clinical endocrinology and metabolism, 2010)
The study investigated the regulation of matrix metalloproteinases (MMP)-9 in obesity-associated insulin resistance in humans. The objectives of the investigation were to study MMP-9 regulation by insulin resistance and pioglitazone treatment in impaired glucose tolerant subjects using adipose tissue biopsies and study the mechanism of MMP-9 regulation by pioglitazone in adipocyte cultures. 86 nondiabetic, weight-stable subjects between 21 and 66 yr of age were recruited in a university hospital research center setting. All subjects underwent a sc adipose tissue incisional biopsy from the lower abdominal wall and insulin sensitivity testing using a frequently sampled iv glucose tolerance test. Impaired glucose-tolerant subjects were randomized to receive metformin or pioglitazone for 10 wk. To study the mechanism of MMP-9 regulation in adipocytes, cells were treated with pioglitazone or protein kinase C alpha antisense oligomers, and MMP-9 levels were examined. There was a positive correlation between MMP-9 and body mass index (r = 0.40, P < 0.01) and negative correlation between MMP-9 and insulin sensitivity (r = -0.46, P < 0.001). The improvement in insulin sensitivity from pioglitazone resulted in a 52 +/- 0.2% reduction in MMP-9 mRNA. Fractionation of adipose tissue indicated that MMP-9 was mostly in the stromal vascular fraction. Pioglitazone also decreased MMP-9 in 3T3-F442A adipocytes and THP1 macrophages. Coculture of adipocytes with macrophages augmented MMP-9 expression in adipocytes and pioglitazone decreased MMP-9 in both adipocytes and macrophages. These data indicate that MMP-9 is elevated in insulin resistance and is reduced by pioglitazone.